Analysis Of Gut Microbiota Diversity In Individuals With Traditional Fermented Food Consumption Patterns - Rezqiqah Aulia Rahmat; Anastasia A. Basir (International Journal of Health Sciences, 2026)
Gut microbiota play an important role in maintaining human health, including metabolism, immune function, and gastrointestinal health. Traditional fermented foods contain various probiotic microorganisms that may influence the composition and diversity of gut microbiota. However, evidence regarding the relationship between traditional fermented food consumption and gut microbiota diversity remains limited, particularly among Indonesian populations. This study aims to analyze the diversity of gut microbiota among individuals with different traditional fermented food consumption patterns. This study used a quantitative approach with an analytical observational design employing a cross-sectional method. The study involved 80 adults aged 20–50 years who were categorized into high and low fermented food consumption groups based on Food Frequency Questionnaire (FFQ) results. Fecal samples were collected and analyzed using 16S rRNA gene sequencing. Gut microbial diversity was assessed using the Shannon-Wiener, Chao1, and Simpson diversity indices. Data analysis was performed using the Independent t-test and Spearman correlation test.The results showed that participants with high traditional fermented food consumption had significantly higher Shannon-Wiener diversity indices compared to those with low consumption (4.52 ± 0.38 vs. 3.89 ± 0.41; p < 0.001). In addition, the relative abundances of beneficial bacterial genera, including Lactobacillus, Bifidobacterium, and Faecalibacterium, were significantly greater in the high-consumption group. Statistical analysis also revealed a positive correlation between fermented food consumption frequency and gut microbiota diversity (r = 0.621; p < 0.001). The study concludes that traditional fermented food consumption is associated with greater gut microbiota diversity and increased abundance of beneficial bacterial taxa. These findings suggest that regular consumption of traditional fermented foods may contribute positively to gut health and overall well-being